Architecture of the ciliary muscle of Gallus domesticus - Tedesco, Roberto Carlos [UNIFESP] (2005)
There are species-related anatomical differences in the ciliary muscle of the avian eye. the arrangement of muscular fibers in the avian eye is not well defined. To clarify this situation, we studied the architecture of ciliary muscle of Gallus domesticus by light and scanning electron microscopy (SEM). Our results showed the existence of three main muscular groups that we defined as anterior, posterior, and intermediary. These muscle divisions correspond to the description of the ciliary muscle as previously stated by Crampton (1813), Brucke, and Muller (1856). the striated fibers have a meridian orientation. the anterior and posterior muscular groups are inserted in the sclera, around the Schlemm's canal wall and ciliary process stroma. the vitreal intermediary muscle has fibers inserted in Schlemm's canal wall and ciliary process stroma. the framework of these muscular fibers may according to its insertions participate in the visual accommodation mechanism and outflow of the aqueous humor system. © 2005 Wiley-Liss, Inc.